2013
DOI: 10.1007/s10722-012-9947-y
|View full text |Cite
|
Sign up to set email alerts
|

HPTLC analysis of guggulsterone isomers in Commiphora wightii (Arn.) Bhandari: an endangered oleo-gum resin species heading towards extinction

Abstract: The oleo-gum resin of Commiphora wightii (Arn.) Bhandari, a pharmacologically important balsamiferous woody shrub, has been used in treating various ailments and disorders since ancient times (2000 B.C.) due to the presence of steroidal compound guggulsterone. Two bioactive isomers of guggulsterone, E and Z, are responsible for lipid-and cholesterollowering and anti-cancerous activities. Further, guggul has been approved as food supplement by US-FDA as well as Council of Europe. Indiscriminate harvest of C. wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…These outcomes depicted that wild mature guggul plants (more than eight years of age) growing in adverse conditions or in rocky tracts had more guggulsterone content. Variation in guggulsterone content among accessions has also been reported by Kulhari et al (2013); Soni et al (2010) and Yadav et al (1999). Soni et al (2010) attributed the discrepancy in guggulsterone content to environmental factors like temperature and rainfall of the concerned geographical region; higher guggulsterone content was obtained during summer (May-July, highest in May) which gradually decreased in the rainy season (Aug-Oct) and was lowest in winter (Nov-March).…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…These outcomes depicted that wild mature guggul plants (more than eight years of age) growing in adverse conditions or in rocky tracts had more guggulsterone content. Variation in guggulsterone content among accessions has also been reported by Kulhari et al (2013); Soni et al (2010) and Yadav et al (1999). Soni et al (2010) attributed the discrepancy in guggulsterone content to environmental factors like temperature and rainfall of the concerned geographical region; higher guggulsterone content was obtained during summer (May-July, highest in May) which gradually decreased in the rainy season (Aug-Oct) and was lowest in winter (Nov-March).…”
Section: Resultssupporting
confidence: 64%
“…Preliminary results indicated that negligible amount of guggulsterone isomers were detectable in the leaf and root samples of C. wightii, therefore, only the stem samples showing presence of substantial quantity of guggulsterone were taken up for further studies. The oleogum resin is mainly found in the stem only therefore, selective distribution of the resin and its components is expected (Kulhari et al 2013). The E and Z isomers of guggulsterone, individual as well as mixture, depicted a clear peak during separation at a retention time of 15.009 and 17.809 min., respectively.…”
Section: Resultsmentioning
confidence: 98%
“…Silica gel 60 F 254 -coated aluminum plate as a stationary phase used in more than 80% of HPTLC analysis for the quantification of compound. In context with mobile phase, various combinations of organic solvents were used for GS estimation like light petroleum: ethyl acetate (3:1),[ 41 ] n-hexane: chloroform: ethyl acetate: methanol in (10:3:3:1),[ 39 ] toluene: acetone with the ratio of 9:1[ 42 43 44 ] and 9.3:0.7[ 45 ] and petroleum ether: ethyl acetate: methanol (6:2:0.5). [ 40 ] In addition to these combinations of solvent toluene: ethyl acetate: formic acid: methanol (6:2:1:0.5) solution is preferred for quantitative estimation of GS in the herbal formulations.…”
Section: Discussionmentioning
confidence: 99%
“…Mean detected values of guggulsterone-E and guggulsterone-Z were 730.28 and 710.84 μg/g in UHPLC, and 692.97 and 699.87 μg/g in HPTLC, respectively, showing prominence of these two core ingredients of MYG. These cis and trans isomers (guggulsterone-E and guggulsterone-Z) have been estimated by many researchers in raw material (gum-resin, stem, leaf, and root) of Commiphora wightii [52,53] and its commercial formulations [54]. This is worth mentioning that simultaneous, rapid determination of guggulsterones and other signature components of MYG has still been underexplored.…”
Section: Comparative Quantitative Analysis Of Myg Using Uhplc and Hptlcmentioning
confidence: 99%